2018
DOI: 10.1108/ajim-02-2018-0030
|View full text |Cite
|
Sign up to set email alerts
|

Information behaviour of architecture students in creative design projects

Abstract: Purpose The purpose of this paper is to report on an exploratory study of third-year architecture students’ information behaviour. It focusses on information activities, personal experience, resource usage, preferences in working individually or collaboratively, preferences for information resources inspiring creativity and physical spaces to be creative. Design/methodology/approach It was a mixed methods study with a strongly qualitative component and limited descriptive quantitative data. Data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Campbell (2017, Table 1, p. 769) revealed architectural faculty have a strong preference for printed materials, coupled with an aversion to the suggestion of cancelling print journals in favor of electronic journals. Meyer and Fourie (2018) found that resource format preferences appear to be tied to an individual's perceived comfort level for use and access, highlighting and emphasizing the subtleties that exist amongst individual users who may be more comfortable navigating within a physical and/or digital realm. Robinson's (2010) comparison study of print and electronic journals, while more from the perspective of collection management captures key points related to the discrepancies of print versus electronic journals, most importantly concerns related to image quality, a desire to have print available to support browsing and loss of content.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Campbell (2017, Table 1, p. 769) revealed architectural faculty have a strong preference for printed materials, coupled with an aversion to the suggestion of cancelling print journals in favor of electronic journals. Meyer and Fourie (2018) found that resource format preferences appear to be tied to an individual's perceived comfort level for use and access, highlighting and emphasizing the subtleties that exist amongst individual users who may be more comfortable navigating within a physical and/or digital realm. Robinson's (2010) comparison study of print and electronic journals, while more from the perspective of collection management captures key points related to the discrepancies of print versus electronic journals, most importantly concerns related to image quality, a desire to have print available to support browsing and loss of content.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Information seeking extends beyond mere data gathering; it extends to the integration of diverse information sources into the creative process, influencing inspiration, ideation, and execution (Ferrara, 2017;Lee et al, 2005). Most information is accessed via the internet and social networks, with traditional printed tools and libraries serving as valuable supplements (Mason and Robinson, 2011), creating a supportive and, information-rich environment for practitioners (Annemans et al, 2014;Meyer and Fourie, 2018;Willson, 2022).…”
Section: Creative Information Practicesmentioning
confidence: 99%
“…Information literacy is crucial in shaping creative information practices. It resides in the experiences, skills, and intuitions of practitioners (McKenzie, 2009;Moring and Lloyd-Zantiotis, 2013;Nicolini, 2016), influencing how people interpret and personally experience a creative information practice (Medaille, 2010;Meyer and Fourie, 2018;Tulloch, 2022). In information practices, information literacy is co-constructed by individuals sharing the same information landscape (Lloyd, 2010b).…”
Section: Creative Information Practicesmentioning
confidence: 99%
“…Meyer and Fourie (2018, p. 422) describe the physical spaces of design studios as venues for sharing notions. Design pinup spaces, which are used for critiquing designs, enable cross-pollination across all years of study, whereas the atrium spaces for design critiques (known by students as design crits) provide observers with interesting insights.…”
Section: Literature Reviewmentioning
confidence: 99%